2009
DOI: 10.1007/s12010-009-8671-3
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Variables Influencing the Clavulanic Acid Production by Streptomyces DAUFPE 3060 Strain

Abstract: Clavulanic acid (CA) is a beta-lactam antibiotic, which has a potent beta-lactamase inhibiting activity. The influence of five variables, namely pH (6.0, 6.4, and 6.8), temperature (28 degrees C, 30 degrees C, and 32 degrees C), agitation intensity (150, 200, and 250 rpm), glycerol concentration (5.0, 7.5, and 10 g/L) and soybean flour concentration (5.0, 12.5, and 20 g/L), on CA production by a new isolate of Streptomyces (DAUFPE 3060) was investigated in 250-mL Erlenmeyer flasks using a fractional factorial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…The experimental design was composed of seven runs, including three repetitions of the central point (Table ) needed to calculate the pure error . Consistently with the results of conventional fermentation in shake flasks, maximum CA production was obtained after 48 h of extractive fermentation in the central point runs; thus, this time was selected as a reference for both responses. A linear regression model was employed to predict each response ( Y ): Y=b0+bixi+bjxj+bijxixj where b 0 is the intercept coefficient, b i and b j are the linear coefficients, b ij is the interaction coefficient and x i and x j are the coded values of the independent variables, namely the aeration rate ( x 1 ) and the agitation rate ( x 2 ).…”
Section: Methodssupporting
confidence: 54%
See 1 more Smart Citation
“…The experimental design was composed of seven runs, including three repetitions of the central point (Table ) needed to calculate the pure error . Consistently with the results of conventional fermentation in shake flasks, maximum CA production was obtained after 48 h of extractive fermentation in the central point runs; thus, this time was selected as a reference for both responses. A linear regression model was employed to predict each response ( Y ): Y=b0+bixi+bjxj+bijxixj where b 0 is the intercept coefficient, b i and b j are the linear coefficients, b ij is the interaction coefficient and x i and x j are the coded values of the independent variables, namely the aeration rate ( x 1 ) and the agitation rate ( x 2 ).…”
Section: Methodssupporting
confidence: 54%
“…The experimental design was composed of seven runs, including three repetitions of the central point (Table 1) needed to calculate the pure error. 28 Consistently with the results of conventional fermentation in shake flasks, 29,30 maximum CA production was obtained after 48 h of extractive fermentation in the central point runs; thus, this time was selected as a reference for both responses. A linear regression model was employed to predict each response (Y):…”
Section: Experimental Designmentioning
confidence: 80%
“…The concentration of CA, taken as dependent variable, was evaluated after 96 h, because previous experiments demonstrated that CA degradation begins after this time 19. The quadratic model to predict the optimal point was expressed by the equation: where b ii are the quadratic coefficients.…”
Section: Experimental Designsmentioning
confidence: 99%
“…CA is a potent antibiotic inhibitor of "serine" (or classes A, C, and D) ␤-lactamases. It is used in conjunction with amoxicillin in a salt (potassium clavulanate) form and prescribed clinically as co-amoxiclav (Augmentin TM in USA, Clavulin TM in Brazil) or with ticarcillin (Timentin TM ) [4].…”
Section: Introductionmentioning
confidence: 99%